2011
DOI: 10.1108/17479891111206328
|View full text |Cite
|
Sign up to set email alerts
|

Exploring migrants' health seeking strategies: the case of Latin American migrants in London

Abstract: Purpose -The objective of this paper is to examine the health seeking strategies of Latin American migrants in London.Design/methodology/approach -The paper draws on a small case study analysis conducted with Latin American migrants in London and relevant stakeholders. Findings -The paper highlights that even where Latin American migrants do have entitlements to use the NHS, a series of informal barriers limits their access. As a consequence many employ a range of transnational health-seeking strategies in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…El fenómeno migratorio puede aumentar la vulnerabilidad de los migrantes y refugiados a padecer problemas de salud debido a mayores exposiciones a factores de riesgo durante el viaje migratorio, violencia sexual y física, condiciones laborales desfavorables y malas condiciones de vida, además de inseguridad alimentaria (7) . De igual forma, pueden existir motivaciones para la migración relacionadas a búsqueda de atención médica en el país receptor (8,9) . Si bien existen tratados internacionales de protección a los derechos humanos del migrante (10,11) , esta población suele enfrentar barreras para su atención en salud, presentando un menor uso de estos servicios respecto a la población local, ya sea por falta de documentación, accesibilidad geográfica o poder adquisitivo (9,12,13) .…”
Section: Mensajes Clave Introducciónunclassified
“…El fenómeno migratorio puede aumentar la vulnerabilidad de los migrantes y refugiados a padecer problemas de salud debido a mayores exposiciones a factores de riesgo durante el viaje migratorio, violencia sexual y física, condiciones laborales desfavorables y malas condiciones de vida, además de inseguridad alimentaria (7) . De igual forma, pueden existir motivaciones para la migración relacionadas a búsqueda de atención médica en el país receptor (8,9) . Si bien existen tratados internacionales de protección a los derechos humanos del migrante (10,11) , esta población suele enfrentar barreras para su atención en salud, presentando un menor uso de estos servicios respecto a la población local, ya sea por falta de documentación, accesibilidad geográfica o poder adquisitivo (9,12,13) .…”
Section: Mensajes Clave Introducciónunclassified
“…Barriers may be structural, social or cultural or may relate to the challenges facing refugee and minority ethnic community organisations, which often become the key source of support in the absence of, or restrictions in, statutory provision (Straimer, 2011;Ward et al, 2008). While access to healthcare is dependent on formal policies, informal networks and support are also significant; language barriers, gender norms and stigmatisation mean that people may rely on receiving information from informal sources, such as from relatives, friends and neighbours (Gideon, 2011;Sabates-Wheeler and MacAuslan, 2007). Further difficulties are caused by the way that asylum support is structured and provisioned.…”
Section: Introductionmentioning
confidence: 99%
“…Mexican migrants sought care from the Mexican health providers in the US not only for the physical problem but also to deal with the spiritual risk and gain emotional support [16]. The majority of the Latin American migrants in a qualitative study reported having utilized the healthcare services from the Latin American or Spanish-speaking doctors in London [17]. In this study, the participants visited the TCM clinics mainly because it is easy to contact and communicate with the doctors.…”
Section: Discussionmentioning
confidence: 99%